B1-level flame-retardant coaxial feeder line for low-loss super-flexible chamber distribution
By adopting a combined structure of composite coating fine copper wire tows, polytetrafluoroethylene insulation layer, coated copper wire shielding layer, elastic polyester fiber layer and modified rubber sheath layer, the problem of traditional RF coaxial feeders poor performance in complex indoor environments is solved, and coaxial feeders with low loss, ultra-flexible and high-level flame retardant performance are achieved.
Patent Information
- Application Number
- CN202510372083.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Traditional RF coaxial feeders perform poorly in complex indoor environments, including conductor deformation, insulating layer damage, signal attenuation, flame retardant performance not meeting the standards and insufficient mechanical performance, making it difficult to meet the low insertion loss and high flame retardant requirements of 5G indoor coverage.
The combined structure of composite coating fine copper wire tows, polytetrafluoroethylene insulating layer, coated copper wire shielding layer, elastic polyester fiber layer and modified rubber sheath layer is adopted. The conductor strength and wear resistance are improved through the equal gradient structure of coated copper wire and nitriding treatment, the polytetrafluoroethylene insulating layer reduces signal attenuation, and the elastic polyester fiber layer and modified rubber sheath layer improve mechanical properties and flame retardant properties.
The coaxial feeder with low loss, ultra-flexibility and high-level flame retardant properties can be bent multiple times in complex indoor environments and maintain good signal transmission performance and fire safety.
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_13
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a low-loss ultra-flexible indoor-use B1-class flame-retardant coaxial feeder. Background Art
[0002] In the implementation of indoor distribution systems (DAS), the performance of RF coaxial feeders, as key components of signal transmission, has a decisive impact on the stability of the communication system, transmission efficiency, and construction flexibility. With the increasing complexity of modern building structures, especially in specific environments such as high-rise buildings, commercial complexes, and underground transportation hubs, the laying of feeders often needs to pass through confined spaces such as closed ceilings, narrow corners, and elevator shafts.
[0003] However, traditional RF cables face several technical challenges in practical applications, which limit their performance in complex indoor environments. The conductors of traditional coaxial feeders are mostly made of rigid corrugated copper or aluminum tube structures, which are repeatedly bent in a small space, easily causing conductor deformation and insulation damage. Secondly, the insulation layer materials of traditional cables (such as foamed polyethylene) have high dielectric constants and loss tangent values, which will cause significant skin effects in high frequency bands (such as 2.6GHz, 3.5GHz), thereby exacerbating signal attenuation. This high transmission loss makes it difficult to meet the strict requirements of 5G indoor coverage for low insertion loss (less than 0.1dB / m@3.5GHz).
[0004] Although ordinary flame-retardant cables can meet the B2 flame-retardant standard, they will produce a lot of smoke and toxic gases (such as HCl, HBr) when burning, which does not meet the strict requirements of B1 flame retardant (peak heat release rate ≤30kW, smoke density level ≤75, burning drops / particles ≤0) in GB31247-2014 "Classification of Combustion Performance of Cables and Optical Cables". Therefore, they have fire safety hazards.
[0005] Traditional cables also have deficiencies in environmental adaptability. For example, in scenes such as elevator shafts, where vibrations and temperature and humidity change frequently, the sheath material of traditional cables has poor fatigue resistance, and after long-term use, problems such as sheath cracking and shield oxidation are prone to occur, which will seriously affect the life of the system.
[0006] In response to the above problems, existing technologies have attempted to improve them by optimizing the foaming process, using flexible braided outer conductors, or adding flame retardants. However, these improvement measures still have some contradictions, such as the mutual constraints between bending performance and transmission loss, and the difficulty in balancing flame retardant efficiency and environmental protection requirements. Therefore, there is an urgent need to develop a new type of coaxial feeder that should have an ultra-flexible structure, low loss characteristics, and high-level flame retardant properties to meet the high-quality communication needs in complex indoor scenarios. Summary of the invention
[0007] The object of the present invention is to provide a low-loss ultra-flexible indoor use B1 class flame-retardant coaxial feeder to solve the problems existing in the prior art.
[0008] In order to solve the above technical problems, on the one hand, the present invention provides a low-loss ultra-flexible B1-class flame-retardant coaxial feeder for indoor distribution, wherein the low-loss ultra-flexible B1-class flame-retardant coaxial feeder for indoor distribution comprises a composite coated fine copper wire bundle, a polytetrafluoroethylene insulation layer, a coated copper wire shielding layer, an elastic polyester fiber layer, and a modified rubber sheath layer; The coated fine copper wire bundle is prepared by twisting and bundling the coated copper wires; the coated copper wire shielding layer is prepared by weaving the coated copper wires into a mesh; wherein the preparation method of the coated copper wire is as follows: placing a copper wire with a diameter of 0.15 mm in an unbalanced magnetron sputtering device, depositing it by magnetron sputtering in a nitrogen-containing atmosphere with a silver-zirconium binary material as a target, and then placing it in an ion nitriding device, evacuating it to below 15 Pa, and then introducing ammonia gas, the gas pressure is maintained at 200 Pa, the furnace temperature is increased to 500-520° C., and then plasma nitriding surface treatment is performed, the heat preservation time is 15 minutes, and after the treatment is completed, the furnace is cooled to room temperature; The modified rubber sheath layer is prepared by mixing, vulcanizing and extruding 75-115 parts of modified rubber, 18-26 parts of modified vermiculite, 6-10 parts of stearic acid, 4-10 parts of carbon black and 2.6-3.8 parts of sulfur; The modified rubber is prepared by grafting modified EPDM rubber with a hydroxyl-containing conjugated diene monomer.
[0009] The present invention weaves a copper wire shielding layer and an elastic polyester fiber layer, reduces the probability of shielding layer movement, reduces internal wear, and thus extends the service life of the cable; in addition, when the modified rubber is used as a sheath raw material and hot-extruded onto the surface of the fiber layer, the flow pressure of the rubber causes it to tightly wrap around the fiber, filling tiny depressions and pores on the fiber surface to form a mechanical fit; when the cable is subjected to an external force, the mechanical fit portion can withstand a portion of the external force, thereby enhancing the bonding stability and thus enhancing the overall mechanical properties of the cable.
[0010] Furthermore, the preparation method of the coated copper wire is as follows: placing a copper wire with a diameter of 0.15 mm in an unbalanced magnetron sputtering device, depositing it by magnetron sputtering in a nitrogen-containing atmosphere with a silver-zirconium binary material as a target, and then placing it in an ion nitriding device, evacuating it to below 15 Pa and then introducing ammonia gas, maintaining the gas pressure at 200 Pa, raising the furnace temperature to 500° C., and then performing plasma nitriding surface treatment for 15 minutes. After the treatment is completed, cooling it to room temperature with the furnace to obtain the coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 22%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere is 1:1.2, the deposition power of magnetron sputtering is 50kW, and the thickness of the surface film layer is 10nm; the present invention firstly uniformly plates silver and zirconium ions on the surface of the copper wire through an unbalanced magnetron sputtering device, and the zirconium-silver ions and the copper wire form an isogradient structure, uniformly distribute the external stress, reduce the phenomenon of internal vibration friction damaging the copper wire, and significantly improve the overall strength of the cable; then, after plasma nitriding treatment, when the copper wires rub against each other, the presence of the nitride layer can reduce the direct contact between the metals, thereby reducing the wear between the conductors, and further realizing multiple bending.
[0011] Furthermore, the hydroxyl-containing conjugated diene monomer is one of 2,4-heptadiene-1-ol, trans-2,4-hexadiene-1-ol and 2,4-octadiene-1-ol.
[0012] Furthermore, the preparation method of the modified vermiculite is as follows: 50 parts by mass of hydroxylated vermiculite powder, 50-100 parts by mass of acrylic acid, and 16-20 parts by mass of water are mixed, stirred evenly, 5-15 parts by mass of silver nitrate solution are added dropwise at 30°C, stirred while adding dropwise, and then allowed to stand for 2 hours, and then 0.4-3 parts by mass of initiator are added, stirred at 60-90°C for 1-2 hours, and after the stirring is completed, filtered, washed with water, dried, and carbonized.
[0013] Furthermore, the initiator is a peroxide or a persulfide.
[0014] Furthermore, the persulfide is potassium persulfate, and the peroxide is cumene hydroperoxide.
[0015] Furthermore, the particle size of the vermiculite powder is 200 mesh.
[0016] Furthermore, the stirring is performed at a speed of 150-300 r / min.
[0017] Furthermore, the specific process of the carbonization is as follows: the carbonization furnace is fed, nitrogen is introduced under normal pressure, the temperature is raised to 160-220°C at 5-10°C / min, after the temperature stabilizes, it is kept warm for 30-50min, air is introduced, the temperature is raised to 250-320°C at 3-6°C / min, after the temperature stabilizes, it is kept warm for 60-120min, nitrogen is introduced, the temperature is raised to 600-650°C at 3-6°C / min, after the temperature stabilizes, it is kept warm for 20-40min.
[0018] Furthermore, the concentration of the silver nitrate solution is 1 mol / L.
[0019] On the other hand, the low-loss ultra-flexible indoor B1-level flame-retardant coaxial feeder is applied to indoor DAS system.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. Modified rubber: First, ethylene-propylene rubber is modified with a hydroxyl-containing conjugated diene monomer to functionalize its hydroxyl group. The presence of polar groups improves compatibility and adhesion with other materials, and can promote the vulcanization process, enhance the cross-linked network structure, reduce the negative effects of additives on it, and improve the mechanical strength of the cable. The present invention introduces conjugated diene as the third monomer to promote the formation of a denser cross-linked network, thereby improving tensile strength, elasticity and wear resistance, and can also improve compatibility with fillers or other polymers; then the modified vermiculite is filled and modified to significantly enhance the mechanical strength and flame retardant properties of the cable. The presence of the coating layer on the surface of the vermiculite not only improves the compatibility between the rubber and the modified vermiculite, but also improves the interaction between the interfaces, thereby further improving the mechanical, antioxidant and flame retardant properties of the coaxial feeder. Through this double modification process, the overall performance of the cable has been significantly improved, so that it exhibits more excellent mechanical properties in practical applications.
[0021] 2. The present invention uses copper as the substrate and silver-plated outer surface and zirconium as the inner conductor. The zirconium-silver ions and the copper wire form an isogradient structure, which evenly distributes the external stress, reduces the phenomenon of internal vibration and friction damaging the copper wire, and significantly improves the overall strength of the cable. After plasma nitriding treatment, when the copper wires rub against each other, the presence of the nitride layer can reduce the direct contact between the metals, thereby reducing the wear between the conductors and achieving multiple bending. The present invention also uses polytetrafluoroethylene as the insulating layer, which reduces the cable loss, thereby reducing the signal attenuation during the transmission process.
[0022] 3. In the present invention, the surface coating of the copper wire, the polytetrafluoroethylene insulation layer and the sheath layer have similar plastic toughness, so that the inner layers can be deformed synchronously during multiple bending deformations, and relative mechanical displacement is not easy to occur. At the same time, the present invention also lays a flexible elastic polyester fiber layer, thereby achieving multiple bending.
[0023] 4. The coaxial feeder of the present invention can be used in indoor DAS systems to solve the problem that the laying of RF cables is affected by the location of the site, especially in narrow areas such as corner corridors with closed ceilings and elevator shafts. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] Example 1: (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 65°C in a nitrogen atmosphere, 2,4-heptadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene rubber, 2,4-heptadiene-1-ol and azobisisobutyronitrile was 1:0.05:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is increased to 500° C., and then a plasma nitriding surface treatment is performed. The heat preservation time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 22%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.2, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 50 parts by weight of acrylic acid and 16 parts by weight of water were mixed and stirred evenly, and then 5 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 150 r / min while being added dropwise. The mixture was then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added. The mixture was stirred at 60°C and 150 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 160°C at a rate of 5°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes. Air was then introduced, and the temperature was increased to 250°C at a rate of 3°C / min. After the temperature stabilized, the mixture was kept warm for 60 minutes. Nitrogen was then introduced, and the temperature was increased to 600°C at a rate of 3°C / min. After the temperature stabilized, the mixture was kept warm for 20 minutes to obtain modified vermiculite. (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 30°, a 0.2 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.05 mm and a braiding temperature of 80°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 75 parts of modified rubber, 18 parts of modified vermiculite, 6 parts of stearic acid, 4 parts of carbon black, and 2.6 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 2 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0026] Example 2: (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 70°C in a nitrogen atmosphere, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile was 1:0.06:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is raised to 520° C., and then a plasma nitriding surface treatment is performed. The holding time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 24%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes, and then air was introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes, and then nitrogen was introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0027] Example 3: (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 75°C in a nitrogen atmosphere, 2,4-octadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene rubber, 2,4-octadiene-1-ol and azobisisobutyronitrile was 1:0.07:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is raised to 520° C., and then a plasma nitriding surface treatment is performed. The heat preservation time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 26%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.5, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 100 parts by weight of acrylic acid and 20 parts by weight of water were mixed and stirred evenly, and then 15 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 220°C at a rate of 10°C / min. After the temperature stabilized, the mixture was kept warm for 50 minutes, and then air was introduced, and the temperature was increased to 320°C at a rate of 6°C / min. After the temperature stabilized, the mixture was kept warm for 120 minutes. Then nitrogen was introduced, and the temperature was increased to 650°C at a rate of 4°C / min. After the temperature stabilized, the mixture was kept warm for 430 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 38°, a 0.4 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.15 mm and a braiding temperature of 100°C. The elastic polyester fiber is item number 1008 and is provided by Yangzhou Tianlun Fiber Co., Ltd. Subsequently, 115 parts of modified rubber, 26 parts of modified vermiculite, 10 parts of stearic acid, 10 parts of carbon black, and 3.8 parts of sulfur are mixed and vulcanized at 150°C and 11MPa for 17 minutes and at 215°C for 1 hour. Subsequently, the mixed material is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 4 mm. The mixed material is naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0028] The coaxial feeder of Examples 1 to 3 was tested for performance: (1) Attenuation test: The coaxial feeder of the present invention is placed under the test conditions of 1 standard atmospheric pressure, horizontal plane and 25°C. After the components are installed, the attenuation of the 10m coaxial feeder is tested and the attenuation value per meter is calculated. Typical attenuation indicators are shown in Table 1.
[0029]
[0030] As can be seen from Table 1, the coaxial feeder prepared by the present invention has small attenuation values at high and low frequencies, so that the transmission distance and transmission effect of the cable are good, and the cable has the characteristics of low transmission loss and resistance to signal interference.
[0031] (2) Flame retardant performance test:
[0032] It can be seen from Table 2 and Table 1 that the coaxial feeder prepared by the present invention has good flame retardant performance and can reach B1 flame retardant grade.
[0033] Comparative Example 1 (using only pure copper wire): (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 70°C, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours in a nitrogen atmosphere, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile was 1:0.06:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (3) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise. The mixture was then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added. The mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes. Air was then introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes. Nitrogen was then introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite. (4) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 copper wires with a diameter of 0.15 mm to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery core; (5) The insulating core is placed in a braiding machine, and a copper wire shielding layer with a diameter of 0.15 mm is braided at a braiding angle of 34°. Then, a 0.3 mm thick elastic polyester fiber layer is braided with an elastic polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, vulcanized at 150°C and 11MPa for 17 minutes, and vulcanized at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm. The sheath is naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0034] Comparative Example 2 (only pure silver target is used during sputtering): (1) At 50°C, ethylene propylene diene rubber is added to a flask containing xylene and stirred until it is completely dissolved. At 70°C in a nitrogen atmosphere, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile are added thereto in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile is 1:0.06:0.005. The mixture is precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver target is deposited by magnetron sputtering in a nitrogen atmosphere. Then, it is placed in an ion nitriding device, evacuated to below 15 Pa, and ammonia gas is introduced. The gas pressure is maintained at 200 Pa, and the furnace temperature is raised to 520 ° C. Then, a plasma nitriding surface treatment is performed. The holding time is 15 min. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire. The vacuum degree of the nitrogen atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes, and then air was introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes, and then nitrogen was introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0035] Comparative Example 3 (only pure zirconium target is used for sputtering): (1) At 50°C, ethylene propylene diene rubber is added to a flask containing xylene and stirred until it is completely dissolved. At 70°C, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile are added thereto in sequence and stirred for reaction for 3 hours in a nitrogen atmosphere, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile is 1:0.06:0.005. The mixture is precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a zirconium target is deposited by magnetron sputtering in a nitrogen atmosphere. Then, it is placed in an ion nitriding device, evacuated to below 15 Pa, and ammonia is introduced. The gas pressure is maintained at 200 Pa, and the furnace temperature is raised to 520 ° C. Then, a plasma nitriding surface treatment is performed. The holding time is 15 min. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire. The vacuum degree of the nitrogen atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes, and then air was introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes, and then nitrogen was introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0036] Comparative Example 4 (without plasma nitriding treatment): (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 70°C, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours in a nitrogen atmosphere, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile was 1:0.06:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuum to obtain modified ethylene propylene diene rubber. (2) Placing a copper wire with a diameter of 0.15 mm in an unbalanced magnetron sputtering device, and depositing the copper wire by magnetron sputtering in a nitrogen-containing atmosphere with a silver-zirconium binary material as a target, to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 24%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes, and then air was introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes, and then nitrogen was introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick elastic polyester fiber layer is weaved with an elastic polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0037] Comparative Example 5 (without adding the elastic polyester fiber braided layer): (1) At 50°C, ethylene propylene diene monomer rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 70°C in a nitrogen atmosphere, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile were added in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene monomer rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile was 1:0.06:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain a modified ethylene propylene diene monomer rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is raised to 520° C., and then a plasma nitriding surface treatment is performed. The holding time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 24%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (4) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise, and then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added, and the mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes, and then air was introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes, and then nitrogen was introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite; (5) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (6) The insulating core is placed in a braiding machine, and the coated copper wire shielding layer is braided at a braiding angle of 34°. Then, 95 parts of modified rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed and vulcanized at 150°C and 11MPa for 17 minutes and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the elastic polyester fiber layer to form a sheath with a thickness of 3 mm. The sheath is naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0038] Comparative Example 6 (without adding hydroxyl-containing conjugated diene monomer): (1) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is raised to 520° C., and then a plasma nitriding surface treatment is performed, and the holding time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 24%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (2) 10 g of 200-mesh vermiculite powder and 200 mL of a 30 wt % hydrogen peroxide aqueous solution were uniformly dispersed by ultrasonication for 10 min, heated to 105 °C for reaction for 6 h under mechanical stirring, cooled and centrifuged at 5000 rpm for 5 min, washed three times with deionized water, and dried under vacuum at 80 °C for 5 h to obtain hydroxylated vermiculite powder; (3) 50 parts by weight of hydroxylated vermiculite powder, 75 parts by weight of acrylic acid and 18 parts by weight of water were mixed and stirred evenly, and then 10 parts by weight of 1 mol / L silver nitrate solution was added dropwise at 30°C, and the mixture was stirred at a speed of 200 r / min while being added dropwise. The mixture was then allowed to stand for 2 hours, and then 0.4 parts by weight of potassium persulfate was added. The mixture was stirred at 60°C and 200 r / min for 1 hour. After the stirring was completed, the mixture was filtered, washed with water, dried, and sent to a carbonization furnace. Under normal pressure, nitrogen was introduced, and the temperature was increased to 200°C at 7°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes. Air was then introduced, and the temperature was increased to 300°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 100 minutes. Nitrogen was then introduced, and the temperature was increased to 620°C at 4°C / min. After the temperature stabilized, the mixture was kept warm for 30 minutes to obtain modified vermiculite. (4) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (5) The insulating core is placed in a braiding machine, and after braiding the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick polyester fiber layer is braided with a polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of EPDM rubber, 22 parts of modified vermiculite, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed and vulcanized at 150°C and 11MPa for 17 minutes and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the polyester fiber layer to form a sheath with a thickness of 3 mm. The sheath is naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0039] Comparative Example 7 (using only vermiculite): (1) At 50°C, ethylene propylene diene rubber was added to a flask containing xylene and stirred until it was completely dissolved. At 70°C in a nitrogen atmosphere, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile were added thereto in sequence and stirred for reaction for 3 hours, wherein the mass ratio of ethylene propylene diene rubber, trans-2,4-hexadiene-1-ol and azobisisobutyronitrile was 1:0.06:0.005. The mixture was precipitated with acetone, extracted with N,N-dimethylformamide, and dried in vacuo to obtain modified ethylene propylene diene rubber. (2) A copper wire with a diameter of 0.15 mm is placed in an unbalanced magnetron sputtering device, and a silver-zirconium binary material is used as a target material to be deposited by magnetron sputtering in a nitrogen-containing atmosphere, and then placed in an ion nitriding device, evacuated to below 15 Pa, and then ammonia gas is introduced, and the gas pressure is maintained at 200 Pa. The furnace temperature is raised to 520° C., and then a plasma nitriding surface treatment is performed. The holding time is 15 minutes. After the treatment is completed, the copper wire is cooled to room temperature with the furnace to obtain a coated copper wire; the composition and weight percentage of the silver-zirconium binary material are: Zr is 24%, the balance is Ag and unavoidable impurities, and the vacuum degree of the nitrogen-containing atmosphere is mbar, the volume ratio of nitrogen and argon in the nitrogen-containing atmosphere was 1:1.3, the deposition power of magnetron sputtering was 50 kW, and the surface film thickness was 10 nm; (3) Wrapping polytetrafluoroethylene around the outer periphery of a bundle of 100 composite coated copper wires to form an insulating layer with a thickness of 0.8 mm, thereby obtaining an insulated battery cell; (4) The insulating core is placed in a braiding machine, and after weaving the coated copper wire shielding layer at a braiding angle of 34°, a 0.3 mm thick polyester fiber layer is weaved with a polyester fiber diameter of 0.10 mm and a braiding temperature of 90°C. Among them, the elastic polyester fiber is item number 1008, provided by Yangzhou Tianlun Fiber Co., Ltd., and then 95 parts of modified rubber, 22 parts of vermiculite powder with a particle size of 200 mesh, 8 parts of stearic acid, 7 parts of carbon black, and 3.2 parts of sulfur are mixed, and vulcanized at 150°C and 11MPa for 17 minutes, and at 215°C for 1 hour. Then, it is extruded and coated on the outside of the polyester fiber layer to form a sheath with a thickness of 3 mm, and naturally cooled to room temperature to obtain a low-loss ultra-flexible indoor distribution B1 grade flame-retardant coaxial feeder.
[0040] Three coaxial feed lines prepared in Examples 1-3 and Comparative Examples 1-7 were selected as test samples, and the tensile strength and elongation at break were tested according to the standard of GB / T2951-2008, and the average values of tensile strength and elongation at break of each group were calculated. The results are shown in Table 3.
[0041]
[0042] The bending test machine was used to conduct anti-bending swing tests on the experimental samples 1-3 and the comparative samples 1-7. The cable will not bend excessively at the interface. A heavy object is added to the cable as a load, so that the applied force is 5N. The clamp R = 10mm swing mechanism is used to swing 180° (90° on both sides of the plumb line), the number of swings is 5000, and the swing rate is 30 times per minute. During the test, a current of 0.5A is required; if no breakage occurs after the test, it is recorded as '0', and if a breakage or crack occurs, it is recorded as '1'. The results are shown in Table 4.
[0043]
[0044] Three coaxial feeders prepared in Examples 1-3 and Comparative Examples 1-7 were selected as test samples, and the test samples were subjected to abrasion resistance tests according to the standard of GB / T5013-2008. After the coaxial feeders in each group were subjected to 20,000 one-way movements, the length of the exposed insulation portion of the cable of each group of test samples was recorded, and the average length of the exposed insulation portion of each group of test samples was calculated. The results are shown in Table 5.
[0045]
[0046] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder, characterized in that: The low-loss ultra-flexible indoor distribution B1-level flame-retardant coaxial feeder comprises a composite coated fine copper wire bundle, a polytetrafluoroethylene insulation layer, a coated copper wire shielding layer, an elastic polyester fiber layer, and a modified rubber sheath layer; The coated fine copper wire bundle is prepared by twisting and bundling the coated copper wires; the coated copper wire shielding layer is prepared by weaving the coated copper wires into a mesh; wherein the preparation method of the coated copper wire is as follows: placing a copper wire with a diameter of 0.15 mm in an unbalanced magnetron sputtering device, depositing it by magnetron sputtering in a nitrogen-containing atmosphere with a silver-zirconium binary material as a target, and then placing it in an ion nitriding device, evacuating it to below 15 Pa, and then introducing ammonia gas, maintaining the gas pressure at 200 Pa, raising the furnace temperature to 500-520° C., and then performing plasma nitriding surface treatment, the heat preservation time is 15 minutes, and after the treatment is completed, cooling it to room temperature with the furnace; The modified rubber sheath layer is prepared by mixing, vulcanizing and extruding 75-115 parts of modified rubber, 18-26 parts of modified vermiculite, 6-10 parts of stearic acid, 4-10 parts of carbon black and 2.6-3.8 parts of sulfur; The modified rubber is prepared by grafting modified EPDM rubber with a hydroxyl-containing conjugated diene monomer.
2. According to claim 1, a low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder, characterized in that: The hydroxyl-containing conjugated diene monomer is one of 2,4-heptadiene-1-ol, trans-2,4-hexadiene-1-ol and 2,4-octadiene-1-ol.
3. According to claim 1, a low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder, characterized in that: The preparation method of the modified vermiculite comprises the following steps: 50 parts by weight of hydroxylated vermiculite powder, 50-100 parts by weight of acrylic acid and 16-20 parts by weight of water are mixed, and after being stirred evenly, 5-15 parts by weight of silver nitrate solution is added dropwise at 30° C., and stirred while adding dropwise, and then the mixture is allowed to stand for 2 hours, and then 0.4-3 parts by weight of initiator is added, and the mixture is stirred at 60-90° C. for 1-2 hours, and after the stirring is completed, the mixture is filtered, washed with water, dried and carbonized.
4. According to claim 3, a low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder, characterized in that: The initiator is a peroxide or a persulfide.
5. According to claim 4, a low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder, characterized in that: The persulfide is potassium persulfate, and the peroxide is cumene hydroperoxide.
6. The low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder according to claim 3, characterized in that: The particle size of the vermiculite powder is 200 meshes.
7. The low-loss ultra-flexible B1-level flame-retardant coaxial feeder for indoor use according to claim 3, characterized in that: The stirring is carried out at a speed of 150-300 r / min.
8. The low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder according to claim 3, characterized in that: The specific process of the carbonization is as follows: the carbonized material is put into a carbonization furnace, and nitrogen is introduced under normal pressure to increase the temperature to 160-220°C at a rate of 5-10°C / min. After the temperature stabilizes, the material is kept warm for 30-50 minutes. Air is introduced to increase the temperature to 250-320°C at a rate of 3-6°C / min. After the temperature stabilizes, the material is kept warm for 60-120 minutes. Nitrogen is introduced to increase the temperature to 600-650°C at a rate of 3-6°C / min. After the temperature stabilizes, the material is kept warm for 20-40 minutes.
9. The low-loss ultra-flexible indoor use B1-level flame-retardant coaxial feeder according to claim 3, characterized in that: The concentration of the silver nitrate solution is 1 mol / L.
10. The application of a low-loss ultra-flexible indoor B1 flame-retardant coaxial feeder according to claim 1, characterized in that: The low-loss ultra-flexible indoor B1-level flame-retardant coaxial feeder is applied to indoor DAS systems.
Citation Information
Patent Citations
Corrosion-resistant high-flexibility coaxial cable and preparation process thereof
CN114974737A
Composite insulating material for high-voltage cable accessories and preparation method of composite insulating material
CN116144116A
Surface treatment method for copper wire
CN116162888A
Low-smoke halogen-free flame-retardant cable
CN116386943A